The roadside - Bellamy, David, 1933-2019.; Dow, Jill (New York : C.N. Potter : Distributed by Crown, 1988)
Describes how the construction of a six-lane highway in a wilderness area disrupts the balance of nature and forces the animals there to struggle for existence.
Ill. on lining papers.
Mode of access: Internet.
Keywords: Nature -- Effect of human beings on -- Juvenile literature; Ecology -- Juvenile literature; Roadside ecology -- Juvenile literature; Nature -- Effect of human beings on -- Juvenile literature; Roadside ecology -- Juvenile literature